Transcriptomic signatures shaped by cell proportions shed light on comparative developmental biology - Pantalacci, Sophie; Guéguen, Laurent; Petit, Coraline; Lambert, Anne; Peterkovà, Renata; Sémon, Marie (Genome biology, 2017)
BACKGROUND: Comparative transcriptomics can answer many questions in developmental and evolutionary developmental biology. Most transcriptomic studies start by showing global patterns of variation in transcriptomes that differ between species or organs through developmental time. However, little is known about the kinds of expression differences that shape these patterns. RESULTS: We compared transcriptomes during the development of two morphologically distinct serial organs, the upper and lower first molars of the mouse. We found that these two types of teeth largely share the same gene expression dynamics but that three major transcriptomic signatures distinguish them, all of which are shaped by differences in the relative abundance of different cell types. First, lower/upper molar differences are maintained throughout morphogenesis and stem from differences in the relative abundance of mesenchyme and from constant differences in gene expression within tissues. Second, there are clear time-shift differences in the transcriptomes of the two molars related to cusp tissue abundance. Third, the transcriptomes differ most during early-mid crown morphogenesis, corresponding to exaggerated morphogenetic processes in the upper molar involving fewer mitotic cells but more migrating cells. From these findings, we formulate hypotheses about the mechanisms enabling the two molars to reach different phenotypes. We also successfully applied our approach to forelimb and hindlimb development. CONCLUSIONS: Gene expression in a complex tissue reflects not only transcriptional regulation but also abundance of different cell types. This knowledge provides valuable insights into the cellular processes underpinning differences in organ development. Our approach should be applicable to most comparative developmental contexts.
Keywords: vývojová biologie; mozaicismus; Animals; moláry; epitel; Morphogenesis; Female; organogeneze; Gene Expression Regulation, Developmental; Molar; ženské pohlaví; morfogeneze; Mice; Developmental Biology; Organogenesis; signální transdukce; myši; Signal Transduction; Epithelium; Male; Mesoderm; mezoderm; transkriptom; zvířata; mužské pohlaví; Transcriptome; vývojová regulace genové exprese; Mosaicism